FORMATION OF CULTURE-ORIENTED COMPETENCIES ON THE MATERIAL OF THE AUTHOR’S MANUAL IN LINGUOCULTURAL REGIONAL STUDIES "PSKOV AND ADJACENT BORDERLANDS" - Matsevich, Svetlana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
The article is aimed at redefining linguocultural regional studies role in language education. The increasing role of linguocultural regional studies as an academic discipline is explained as it determines strategy and tactics of implementation of both regional and national component in the humanity education, contributes to national self-identification of an individual in the world culture. In the new learning environment it is this discipline that creates conditions for the integration of the individual in a multicultural and polylingual educational environment. It also contributes to the solvation of the problem of organizing language training in an academic group, members of which are representatives of different ethnic cultures. The attempt of using the extended version of a local region in order to create a multilingual and multicultural learning situation which results from new ways of training organization search is absolutely new and timely. The content and structure of linguistic and regional studies competence is detailed. The linguocultural regional competence is defined. Formation of culture-oriented competences on the material of the author's manual “Pskov and Adjacent Borderlands” is traced. The pattern of learning and the results of education are described and analysed. The methods applied were analytical, project, associative, communicative, testing, modeling and mathematical data processing.